Oneness vs. the 1% shattering illusions, seeding freedom - Shiva, Vandana (White River Junction Chelsea Green Publishing, 2020)
With a new epilogue about Bill Gates's global agenda and how we can resist the billionaires' war on life Widespread poverty and malnutrition, an alarming refugee crisis, social unrest, and economic polarization have become our lived reality as the top 1% of the world's seven-billion-plus population pushes the planet-and all its people-to the social and ecological brink. In Oneness vs. the 1%, Vandana Shiva takes on the Billionaires Club of Gates, Buffet, and Zuckerberg, as well as other modern empires whose blindness to the rights of people, and to the destructive impact of their construct of linear progress, have wrought havoc across the world. Their single-minded pursuit of profit has undemocratically enforced uniformity and monocultures, division and separation, monopolies and external control-over finance, food, energy, information, healthcare, and even relationships. Basing her analysis on explosive, little-known facts, Shiva exposes the 1%'s model of philanthrocapitalism, which is about deploying unaccountable money to bypass democratic structures, derail diversity, and impose totalitarian ideas based on One Science, One Agriculture, and One History. She calls for the "resurgence of real knowledge, real intelligence, real wealth, real work, real well-being," so that people can reclaim their right to: Live Free. Think Free. Breathe Free. Eat Free
Includes bibliographical references and index.
Keywords: Income distribution